ANALISIS PENERAPAN OPEN SOURCE ENTERPRISE RESOURCES PLANNING PADA PROSES PENGAJUAN CUTI KARYAWAN DI INSTITUT TEKNOLOGI DEL (IT DEL) - Parmonangan R. Togatorop (LP2MTBM MAKARIOZ, 2018)
This paper demonstrates the results of analyzing business processes for filing leave or permission for employees at IT Del. The ERP system is a business solution that is applied to increase productivity in the company. ERP systems are a combination of software packages with business processes, therefore ERP implementation and business processes are using open source ERP is an option because it is easier to implement with lower costs. This article discusses the analysis of company business processes and maps with business processes in an ERP system.